How "Full" is "Full Fusion" during Exocytosis from Dense Core Vesicles? Effect of SDS on "Quantal" Release and Final Fusion Pore Size. Issue 9 (1st January 2016) - Hu, Ren; Ren, Bin; Lin, Chang-Jian; Oleinick, Alexander; Svir, Irina; Tian, Zhong-Qun; Amatore, Christian
Abstract : In this work, release was elicited from PC12 using sufficiently small concentrations of sodium dodecyl sulfate (SDS) to perturb normal release mechanism in an attempt to reveal concealed information while keeping physiologically compatible conditions. Amperometry was used to monitor and quantify the released fluxes and kinetics in individual vesicular events. This showed that stimulating release with SDS 350 μM leads to a doubling of the quantity of catecholamine cations released per event and much larger release fluxes as compared to controls (release elicited with K + 105 mM under same conditions) or SDS 250 μM. These quantitative measurements confirm our previous theoretical model and reports based on ex situ cytometric experiments on isolated PC12 vesicles, which established that release is far from being total under normal exocytotic conditions. Secondly, this establishes that the maximal size of fusion pores at the end of the "full fusion" phase is limited by some contraption unrelated to the membrane. Indeed, the present results are entirely consistent with the fact that SDS 350 μM allows the fusion pore to expand to a double size (ca. 28 nm radius) compared to controls and SDS 250 μM (ca. 14 nm radius).